Obstructive sleep apnea in patients with laryngeal cancer after supracricoid or vertical partial laryngectomy - Lei Ouyang; Liang Yi; Lin Wang; Qinglai Tang; Xinming Yang; Shisheng Li (Journal of Otolaryngology - Head and Neck Surgery, 2019)
Abstract Objective To investigate whether partial laryngectomy is a risk factor for obstructive sleep apnea (OSA) and the effect of different partial laryngectomy methods on OSA. Method A prospective study was carried out involving 40 patients who underwent supracricoid partial laryngectomy (SCPL) (24) or vertical partial laryngectomy (VPL) (16) for carcinoma of the larynx. Apnea-hypopnea index (AHI) and oxygen saturation determined by polysomnography (PSG), Epworth sleepiness scale (ESS) score, and body mass index (BMI) were evaluated in patients before surgery, on the day of tracheal tube removal and three months later. In patients who developed apnea, laryngoscopy, Muller’s test, computer tomography (CT) and dynamic sleep magnetic resonance imaging (MRI) were performed to assess the location of airway stenosis and collapse. Results The AHI (P<0.001) increased and the lowest oxygen saturation (P<0.001), ESS score (P<0.001) and BMI (P=0.017) decreased after extubation compared with before surgery. Three months after extubation, the same changes were found in AHI (P<0.001) and the lowest oxygen saturation (P<0.001), but the ESS score (P<0.001) increased compared with that preoperatively. The AHI in the SCPL group was significantly higher than that in the VPL group post-operatively (P=0.010), while the miniSpO2 in the SCPL group was lower than that of the VPL group (P=0.022). Laryngoscopy showed that the patients with partial excision of the larynx had a narrowed retropalatal and retrolingual space post-operatively. Muller's test showed the collapse of the retropalatal and retrolingual space, and the CT scan showed that the tongue root was positioned lower in the SCPL group. Compared with the retropalatal and retrolingual space in the expiratory phase according to dynamic sleep MRI, the space in the inspiratory phase was clearly decreased. Conclusion Laryngeal function preservation surgery for laryngeal cancer results in the occurrence of OSA by altering the anatomical structure of the larynx and pharynx. OSA was more severe in patients undergoing SCPL than in patients undergoing VPL. The effect of partial laryngectomy on OSA may be related to the surgical method used.